2015
DOI: 10.2196/jmir.3985
|View full text |Cite
|
Sign up to set email alerts
|

Expectations Among Patients and Health Professionals Regarding Web-Based Interventions for Depression in Primary Care: A Qualitative Study

Abstract: BackgroundOne-quarter of the world’s population will suffer from depression symptoms at some point in their lives. Mental health services in developed countries are overburdened. Therefore, cost-effective interventions that provide mental health care solutions such as Web-based psychotherapy programs have been proposed.ObjectiveThe intent of the study was to identify expectations regarding Web-based psychotherapy for the treatment of depression in primary care among patients and health professionals that might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 79 publications
4
36
0
3
Order By: Relevance
“…Patients in our study did not make much use of the support offered. We do not know the real reasons for this, but the lack of initial face-to-face contact with the psychotherapist might have hampered the establishment of an adequate alliance—something that might merit interest for further studies [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients in our study did not make much use of the support offered. We do not know the real reasons for this, but the lack of initial face-to-face contact with the psychotherapist might have hampered the establishment of an adequate alliance—something that might merit interest for further studies [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adults presenting with depressive symptoms in PC were randomized to receive either iTAU from their GP or an Internet-based intervention program (Smiling is Fun) for depression, in this case, either with psychotherapist support (LITG) or without it (CSG). The trial protocol of the study [ 16 ], the manual used to implement the program [ 17 ], and a study on expectations of depressed PC patients have already been published [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-adherence to the myCompass program was an issue in the trial and hence the cost-effectiveness analysis. Although non-adherence may have implications for upscaling this intervention, qualitative evidence has shown that in many cases, patients withdraw for personal reasons such as improvement in symptoms (known as “e-attainers”) [ 59 , 60 ], not because of problems with the technology or the social environment [ 61 ]. Including programs such as myCompass as part of an integrated model allows clinicians to monitor interim outcomes and inform decisions on patient treatment pathways, in case some patients are negatively affected by the limitations in effectiveness of low-intensity treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about the clinical effectiveness of mental health services provided through internet-based interventions incited controversy among health care professionals worldwide (Montero-Marín et al, 2015;Du et al, 2013). The ambiguity regarding the effectiveness of iCBT programmes in treating depression and anxiety is apparent.…”
Section: Final)mentioning
confidence: 99%